Differentiating leader hubris and narcissism on the basis of power. (February 2020) - Asad, Sarosh; Sadler-Smith, Eugene
Hubris and narcissism overlap, and although extant research explores relationships between them in terms of characteristics, attributes, and behaviours, we take a different view by analysing their differences in relation to power and leadership. Drawing on a psychology of power perspective, we argue that narcissistic and hubristic leaders relate to and are covetous of power for fundamentally different reasons. Using the metaphor of intoxication, hubrists are intoxicated with positional power and prior success, but for narcissists, power facilitates self-intoxication and represents a means of maintaining a grandiose self-view. Unbridled hubris and narcissism (i.e. searching for and facilitated by unfettered power) have important ramifications for leadership research and practice. Leadership discourse, preoccupied with and predicated on positive aspects of leadership, should assess these two potent aspects of leadership because misuse of power by hubristic and narcissistic leaders can create conditions for, or directly bring about, destructive and sometimes catastrophic unintended outcomes for organizations and society.